2009
DOI: 10.1080/00498250802617746
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of CYP3A4.16: Catalytic activities toward midazolam and carbamazepine

Abstract: 1. To assess the substrate-dependent effects of the low-activity allele of human CYP3A4, CYP3A4*16 (Thr185Ser), a recombinant wild-type (CYP3A4.1) or variant (CYP3A4.16) protein was co-expressed with human NADPH-P450 reductase in Sf21 insect cells using a baculovirus-insect cell system. 2. The holo-CYP3A4 protein level of CYP3A4.16 in insect microsomes was slightly higher than that of CYP3A4.1, while no difference in total (apo- and holo-) CYP3A4 protein levels was observed between them. 3. When midazolam was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Insect cell microsomes coexpressing CYP3A4 (wild type or variants) and NADPH P450 reductase (OR) were prepared according to methods described previously (Maekawa et al, 2009). The cytochrome P450 content and OR activity in microsomes were measured (Phillips and Langdon, 1962;Omura and Sato, 1964), and Western blotting of CYP3A4 and OR was performed as described previously (Maekawa et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insect cell microsomes coexpressing CYP3A4 (wild type or variants) and NADPH P450 reductase (OR) were prepared according to methods described previously (Maekawa et al, 2009). The cytochrome P450 content and OR activity in microsomes were measured (Phillips and Langdon, 1962;Omura and Sato, 1964), and Western blotting of CYP3A4 and OR was performed as described previously (Maekawa et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Catalytic activities for MDZ 1Ј-and 4-hydroxylations and CBZ 10,11-epoxide formation were measured as described previously (Maekawa et al, 2009), with slight modifications. For other substrates (ATV, PTX, DTX, IRN, and TFN), the incubation conditions were similar to those used for MDZ and CBZ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive cooperativity was also detected in the binding of aflatoxin B1 (n H of 2.3) [12], α-naphthoflavone (ANF; n H of 1.2–1.7) [11, 13], and Nile Red [NR] (n H of 1.6) [14]. Acetaminophen and midazolam bind to CYP3A4 with a negative cooperativity [15, 16], whereas progesterone and 7-benzyloxyquinoline (BQ) display both positive and negative cooperativity [10, 17]. Structures of these substrates are shown in Fig.…”
Section: 2 Experimental Approachesmentioning
confidence: 99%
“…Several genetic polymorphisms in CYP3A4 are known to affect its catalytic activity and to contribute in part to interindividual differences in the pharmacokinetics and pharmacodynamics of CYP3A4 substrate drugs. Maekawa et al, demonstrated the substrate dependent altered kinetics of CYP3A4*16 allele for midazolam and CBZ [62,63]. They also found lowered catalytic activities of the two alleles found in East Asians, CYP3A4*16 (Thr185Ser) and CYP3A4*18 (Leu293Pro), for metabolism of some drug substrates, including CBZ compared with wild type allele, CYP3A4*1 [63].…”
Section: Pharmacogenetics Of Carbamazepine Metabolismmentioning
confidence: 91%